Comparison between epidural injection of calcium–naloxone and intramuscular GnRH as therapeutic methods in the treatment of follicular ovarian cysts in dairy cattle - amirali kaveh (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2014)
Ovarian cysts is one of the problems of dairy cattle with high production. The aim of this study was to evaluate the response to treatment of ovarian follicular cysts using calcium naloxone comparison with the conventional method of intramuscular GnRH injection. This study was conducted in third station dairy cattle farming center in Moghan on 54 cows' affected follicular ovarian cysts approximately 100 to 150 days after parturition. Following physical examination and diagnosis of the cystic cows, the animals were divided into three groups. The first group was the control group (5ml GnRH IM), the second group was the treatment group 1 (Nx via epidural injection 2 times with 3 day intervals) and the third group was the treatment group 2 (Ca–Nx via epidural injection 2 times with 3 day intervals and 5 ml of intramuscular GnRH simultaneously with the second Ca-Nx injection). To check the results, the animals was examined two weeks after the last injection. The results indicated that there was a significant difference in luteinization rate between the first and second groups with more luteinization rate in the first group. There was no significant difference between the first and third group in luteinization rate. Also, there was a significant difference in luteinization rate between the second and third group, with more luteinization rate observed in the third group. There was no significant difference between the fertility rate of the treatment and control groups.